Occurrence of medical co-morbidity in mild cognitive impairment: implications for generalisation of MCI research - Stephan, Blossom C. M. (Oxford University Press, 2011)
Background: diagnosis of mild cognitive impairment (MCI) typically excludes individuals with medical co-morbidity. Interest in MCI screening raises the questions of what are the best criteria to identify a representative sample and what factors are associated with MCI progression to dementia.